Simulating the drought response of European tree species with the dynamic vegetation model LPJ-GUESS (v4.1, 97c552c5) - B. F. Meyer; J. P. Darela-Filho; K. Gregor; A. Buras; Q.-L. Gu; A. Krause; D. Liu; P. Papastefanou; S. Asuk; T. E. E. Grams; C. S. Zang; A. Rammig (Geoscientific Model Development, 2025)
Due to climate change, severe-drought events have become increasingly commonplace across Europe in recent decades, with future projections indicating that this trend will likely continue, posing questions about the continued viability of European forests. Observations from the most recent pan-European droughts suggest that these types of “hotter droughts” may acutely alter the carbon balance of European forest ecosystems. However, substantial uncertainty remains regarding the possible future impacts of severe drought on the European forest carbon sink. Dynamic vegetation models can help to shed light on such uncertainties; however, the inclusion of dedicated plant hydraulic architecture modules in these has only recently become more widespread. Such developments intended to improve model performance also tend to add substantial complexity, yet the sensitivity of the models to newly introduced processes is often left undetermined. Here, we describe and evaluate the recently developed mechanistic plant hydraulic architecture version of LPJ-GUESS and provide a parameterization for 12 common European forest tree species. We quantify the uncertainty introduced by the new processes using a variance-based global sensitivity analysis. Additionally, we evaluate the model against water and carbon fluxes from a network of eddy covariance flux sites across Europe. Our results indicate that the new model is able to capture drought-induced patterns of evapotranspiration along an isohydric gradient and manages to reproduce flux observations during drought better than standard LPJ-GUESS does. Further, the sensitivity analysis suggests that hydraulic process related to hydraulic failure and stomatal regulation play the largest roles in shaping the model response to drought.